El crimen organizado y la inimputabilidad de menores reclutados en el Ecuador - Allauca Ortiz, Diana Esthefania (2025)
Organized crime threatens public security and the stability of the State by recruiting minors, taking advantage of their unaccountability to commit crimes, maintain territorial control, and grow economically. This research analyzes the phenomenon in Ecuador from a legal-criminal and doctrinal perspective to strengthen the juvenile justice system and protect the rights of children and adolescents. A qualitative methodology was employed based on a review of national and international legislation (Ecuador, France, and Switzerland), as well as a documentary analysis of organized crime, the recruitment of minors, and the impact of socio-educational measures and rehabilitation programs. Additionally, it was vital to conduct interviews with justice administrators and a prosecutor specializing in adolescent offenders. Subsequently, the results obtained revealed shortcomings in the fulfillment of the purposes of socio-educational measures and rehabilitation programs that fail to disengage minors from criminal networks. Given this situation, the researcher concluded that it is necessary to make structural adjustments to the juvenile justice system to balance the rights of minors with the demands for justice of the victims, in addition to state investment to strengthen rehabilitation programs and policies to reduce the participation, recidivism, and recruitment of minors in criminal activities.